أثر الإلتزام بمعايير الإبلاغ المالي الدولية على الحد من المشاكل المحاسبية المعاصرة - محمد أمين بوراس; محمد فضيل مسايرية (My University, 2022)
World countries, whether weak or strong, face negative impacts related to the outbreak of the accounting problems ,which results from changes in the world, including economic, political...etc. In parallel with these changes, the International Accounting Standards Board (IASB) is trying to cope with this situation by setting reliable standards: IFRS Accounting Standards. Those standards, help in the process of addressing accounting issues. The present study, aimed to discuss the role of the Financial Reporting Standards, in reducing the impact of these problems. To do so, a descriptive approach was carried out through which the study variables were described depending on a relevant literature, then, an investigative approach through a case study was conducted in order to output analysis of a sample of academics' opinions. As a result, the specific items of IFRS been identified to address these problems, and the overall thrust of the sample opinion has been to approve IFRS 'contribution to addressing the effects of accounting problems. ..................................................... تواجه دول العالم سواء الضعيفة منها أو القوية آثاراً سلبية تتعلق بالمشاكل المحاسبية، التي تنتج جرّاء التغيرات التي يواجهها العالم، منها الإقتصادية، السياس يّة...، و موازاتا مع هذه التغيرات تحاول لجنة مجلس معايير الإبلاغ المالي الدولية مواكبتها بإصدار معايير يعتمد عليها في عملية معالجة المشاكل المحاسبية فكان الهدف من هذه الدراسة، تبين دور معايير الإبلاغ المالي في الحدّ من أثر هذه المشاكل، وهذا بإستخدام المنهج الوصفي الذي من خلاله ت وصف متغيرات الدراسة اعتمادا على المراجع المختلفة، والمنهج الإستقصائي من خلال تحليل مخرجات دراسة الحالة لآراء عينة من الأكاديميين. أين تّ التوصّل إلى تحديد الفقرات المحدّدة في معايير الإبلاغ المالي الدولية المعنية بمعالجة تلك المشاكل، وقد كان الإتجاه العام لرأي العينة الموافقة على مساهمة معايير الإبلاغ المالي الدولية في معالجة آثار المشاكل المحاسبية.